Multi-Tiered Dispute Resolution Clauses after UML on Mediation 2018 and the Singapore Convention - Dilek Aydemir (Public and Private International Law Bulletin)
Multi-tiered dispute resolution provides distinct stages, involving separate consecutive ADR procedures for dealing with and seeking to resolve disputes amicably first without a binding result (initial tiers), followed by a binding dispute resolution process, arbitration or litigation, as the last stage for a final and binding decision if the chosen ADR method does not work. Before complying with the ADR procedure in the dispute resolution clause of a contract, when one of the parties directly brings a claim before the arbitral tribunal, it is most likely that the other party will raise an objection regarding the effect of the non-fulfilment of ADR process. How will the tribunal decide regarding the issue? On the one side wording of such MTDR clauses is important on the other side it may be observed that mediation clauses are favourably enforced in comparison with negotiation clauses. Furthermore, the matter whether breach of the contract clause regarding initial ADR clauses is a substantive or procedural issue. Having decided these issues, a further question comes up: what would be the effect of non-fulfilment of such ADR clauses on an arbitration procedure. Of this question, there are several opinions and case reports opposing each other. With the praiseworthy effort of UNCITRAL UML on Mediation and the Singapore Convention together with the ADR rules of certain international dispute resolution institutions may encourage business people to make an effort to solve the disputes by enforcing the ADR procedures in their dispute resolution clauses.